The Influence of Organizational Citizenship Behavior (OCB) and Adversity Quotient on Employee Performance at CV. Mitra Pratiwi - Khairina Maulida Paramitha; Ananda Putri Mawaddah; Ayu Wulan Dari; Muhammad Arif; Fauzan Zulfikar; Lisdayani Lisdayani; Yenti Anita Harahap; Anggia Sari Lubis; Toni Hidayat (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the influence of Organizational Citizenship Behavior (OCB) and Adversity Quotient on employee performance at CV. Mitra Pratiwi. OCB refers to employee voluntary behavior that goes beyond their formal duties, while Adversity Quotient describes an individual's ability to face challenges and work pressures. The research method used is quantitative with data collection techniques through questionnaires. The sample of this study consisted of 50 employees selected using purposive sampling techniques. The results of the study indicate that OCB and Adversity Quotient have a positive and significant influence on employee performance, both simultaneously and partially. This finding confirms that employees with high levels of OCB and good resilience in facing difficulties are more likely to have superior work performance. Therefore, companies need to improve a work culture that encourages positive voluntary behavior and builds employee mental resilience in facing work challenges.